Psychology online personal implications of the internet , boy, girl & games - Ratchill, Sheryl; Black , Barol; Nurshall, John ([Canada] : Access Distribution)
This program explores the online roles of genders and age , as well as the behavioural effect of anonymity. It also looks at the competitive and cooperative aspects of electronic games , from sophisticated multi-user domains to violent'shoot-em-ups'
Editors , Sheryl Ratchill... [et.al.] ; director, Darol Black writer, producer, John Nursall
Host : Jayne Gackenbach
Keywords: Internet; Internet in education; Internet games; World Wide Web